NETWORKING FOR VIOLENCE AGAINST CHILDREN: AN ANALYSIS OF THE FORMAL–INFORMAL NETWORK DICHOTOMY IN UGANDA - Kakuru, Doris M.; Kamusiime, Annah; Kibukamusoke, Martha; Lindner, Kylee; Mugabo, Catherine (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
The rising cases of violence against children (VAC) have prompted strategies, laws, and policies to protect Ugandan children at the grassroots, subnational, and national levels. Despite the emergence of various strategies by different VAC actors who network formally and informally to address VAC, the functionality of their networks has not received adequate attention in previous research. We conducted a qualitative study to examine the dynamics of networking for VAC in Uganda. We collected data using interviews with network funders and leads at the national and subnational levels and focus group discussions with grassroots and community members. Our findings reveal that VAC networks belong to two broad categories: formal and informal. These exist side by side, usually operating in parallel, but sometimes with crisscrossing and overlapping activities. While the work of formal network actors is better resourced and recognized, and more visible, informal network actors are invisibilized in government plans, philanthropic efforts, and scholarly research. A more collaborative and inclusive VAC networking system would be instrumental in enhancing VAC prevention and response.